2015
DOI: 10.1128/mbio.00009-15
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Exposure to Commercial Formulations of the Herbicides Dicamba, 2,4-Dichlorophenoxyacetic Acid, and Glyphosate Cause Changes in Antibiotic Susceptibility in Escherichia coli and Salmonella enterica serovar Typhimurium

Abstract: Biocides, such as herbicides, are routinely tested for toxicity but not for sublethal effects on microbes. Many biocides are known to induce an adaptive multiple-antibiotic resistance phenotype. This can be due to either an increase in the expression of efflux pumps, a reduced synthesis of outer membrane porins, or both. Exposures of Escherichia coli and Salmonella enterica serovar Typhimurium to commercial formulations of three herbicides—dicamba (Kamba), 2,4-dichlorophenoxyacetic acid (2,4-D), and glyphosate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 46 publications
(56 reference statements)
8
144
2
1
Order By: Relevance
“…In contrast, a role of glyphosate in affecting the soil microbial activity is controversially discussed because studies are available suggesting a positive and a negative effect of the herbicide on the microbial activity of the soil (Haney et al, 2002;Barriuso et al, 2011;Schlatter et al, 2017;Dennis et al, 2018). Furthermore, sublethal concentrations of glyphosate were shown to reduce susceptibility of enterobacteria to antibiotics (Kurenbach et al, 2015). Experimental evidence also suggests that aminomethyl-phosphonic acid (AMPA), a breakdown product of glyphosate, may induce chromosomal damage in fish (Guilherme et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a role of glyphosate in affecting the soil microbial activity is controversially discussed because studies are available suggesting a positive and a negative effect of the herbicide on the microbial activity of the soil (Haney et al, 2002;Barriuso et al, 2011;Schlatter et al, 2017;Dennis et al, 2018). Furthermore, sublethal concentrations of glyphosate were shown to reduce susceptibility of enterobacteria to antibiotics (Kurenbach et al, 2015). Experimental evidence also suggests that aminomethyl-phosphonic acid (AMPA), a breakdown product of glyphosate, may induce chromosomal damage in fish (Guilherme et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of glyphosate and bacteria growth have drawn conclusions about the toxicity of glyphosate towards microbes without suitable controls or specifically testing individual components such as glyphosate from a mixture as having an influence without examining it alone or in comparison with positive and nega- tive control. Kurenbach et al 15 have reported that glyphosate can reduce antibiotic susceptibility in Escherichia coli and Salmonella enterica serovar Typhimurium. While these researchers did not investigate glyphosate alone (they evaluated a commercial glyphosate containing product), the claim glyphosate reduced antibiotic sensitivity is not clearly supported by their data; furthermore, many of the test combinations they evaluated appeared to increase antibiotic sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence concerning the neurotoxicity for humans of even low-level exposure to pesticides shows problems with psychomotor speed and visuospatial ability as well as working and visual memory (Bouchard et al 2010;Ross et al 2013). Increasingly common chemicals used in agriculture can induce a multiple antibiotic-resistance phenotype in potential pathogens (Kurenbach et al 2015).…”
Section: Health and Well-being Outcomesmentioning
confidence: 99%